Emotional intelligence, self-esteem, age and gender of learners as correlates of academic self-efficacy of secondary school students from Ibadan, Nigeria (2013)
This study examined the relationship among emotional intelligence, self-esteem. age and gender of learners on the academic self-efficacy of secondary school students. Five hundred and sixty seven students from Ibadan, Oyo State Nigeria responded to a set of Questionnaires consisting of measures of emotional intelligence (EI), self-esteem (SE) and academic self-efficacy (ASE). Hierarchical regression analyses conducted for each dependent variable showed that emotional intelligence, self-esteem and aze predicted students' academic self-efficacy. This research indicates that counselling psvcholozists and teachers should focus on teaching emotional intelligence as a strarezv to develop academic self-efficacy and attitudes of students in all the Nigerian educational institutions. When students are educated to be emotionally and socially intelligent, their general performance can be improved.